Wessen Übersetzung? Möglichkeiten und Grenzen des Begriffs „übersetzerisches Œuvre“ am Beispiel der Klagenfurter Übersetzerin Hertha Lorenz (1916-1989) - Tashinskiy, Aleksey (chronotopos – A Journal of Translation History, 2019)
Hertha Lorenz (1916–1989) was a literary editor, translator and writer from Austria. Over decades, she was closely affiliated with the Klagenfurt-based Eduard Kaiser publishing house. In the publisher’s peritexts, Lorenz is given as either the translator or the editor (“revised by”) of various publications, predominantly European classics of world literature, such as Boccaccio, Charlotte Brontë, Dickens, Dostoyevsky, Dumas, Hugo, Maupassant, Ovid, Poe, Sienkiewicz, Stendhal, Tolstoy or Twain. A historical reconstruction of Lorenz's translatorial oeuvre requires the ability to accurately attribute work to her as an individual and thus needs to disambiguate the translatorship of publications. Here, we have to consider (a) the collaborative-transformative character of translatorial processes on the one hand, and (b) the situatedness of translatorial work within a particular literary and publishing scene on the other. These issues will be addressed on the basis of selected extracts from Lorenz’s work.